Analysis of Student Difficulties in Statistics Courses - Dydik Kurniawan; Tri Wahyuningsih (SAINTIS Publishing, 2018)
The educational implementation is a learning process at all levels, students are required to follow certain lectures, including mathematics courses. Learning difficulties are a barrier to learning where children are not well educated, due to disturbances, both from student factors and external factors. learning, thus students are expected to catch up because of these obstacles. This research is classified into qualitative descriptive research that seeks to describe the analysis of student learning difficulties in statistical subjects. The subjects in this study were the fourth-semester students of 2018/2019 Mulawarman University. Research reveals things that are considered as a barrier factor for students in Statistics. In this study, the researcher collected information through documentation, tests, and interviews with students. The results of the analysis show that the difficulties of students in studying Statistics basically lie in the weakness of the concept. The results of the research conducted by the researcher were the existence of errors in process skills, errors in understanding questions, and errors in using notation. The solution to overcoming these problems is: for the eye teacher of Statistics to be able to develop learning strategies so that students can be more honed in their thinking skills and provide continuous problem training to students.